CONSUMER SATISFACTION KARTU INDOSAT (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Bengkulu) - Onsardi, Onsardi; Maryati, Mia (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The aim of the research is to determine the influence of perceived value and digital marketing on consumer satisfaction among Indosat card customers (case study on students at Muhammadiyah University of Bengkulu. As well as to find out which factors most dominantly influence consumer satisfaction. This research used quantitative methods on 130 respondents. The population used in this research was Indosat card customers among Muhammadiyah Bengkulu University students and sampling in this research was a non-probability sampling technique. The research results concluded that perceived value and digital marketing had a positive and significant effect, both partially and simultaneously, on consumer satisfaction among Indosat customers.Keywords: Perceived Value, Digital Marketing, Consumer Satisfacti